An economic and environmental assessment of carbon capture and storage (CCS) power plants - A case study for the city of Kiel - Sören Lindner; Sonja Peterson; Wilhelm Windhorst (Kiel Institute for the World Economy (IfW), 2009)
In the next years several power plants throughout Europe have to be replaced and the questions is whether to build coal fired power plants with carbon capture and storage (CCS). In a study for the city of Kiel in northern Germany only a 800 MW coal power plant reaches a required minimum rentability. We use the study for an additional economic and environmental evaluation of a coal plant with CCS. We find that integrated gasification combined cycle (IGCC) plants with CCS have in two out of three carbon and energy price scenarios the largest rentability. Pulverized coal (PC) plants with CCS can only compete with other options under very favourable assumptions. Life-cycle emissions from CCS are less than 70% of a coal plant compared to at least more than 80% when only considering direct emissions from plants. Still, life-cycle emissions are lower than in any other assessed option.
Keywords: Q49; Q54; Q59; 330; Coal fired power plants; carbon capture and storage (CCS); cash flow analysis; life cycle analysis; Kohlekraftwerk; Kohlenstoffsenke; Rentabilität; Lebenszyklus; Luftverunreinigung; Emissionshandel; Kosten-Nutzen-Analyse; Kiel